Analyzing the factors affecting coordination in engineer-to-order supply chain. Issue 7 (6th July 2015) - Mello, Mario Henrique; Strandhagen, Jan Ola; Alfnes, Erlend
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Engineer-to-order (ETO) supply chains involve multiple companies for performing complex projects. The ability to effectively coordinate cross-business activities is essential to avoid delays, cost overruns and quality problems. Coordination is related to a number of contingent factors that need to be better comprehended. The purpose of this paper is to highlight such contingent factors and to analyse their effect on the occurrence of project delays. Design/methodology/approach – A multiple case study is used to investigate the moderating factors affecting coordination in projects carried out in an ETO supply chain. Such factors are examined through a cross-analysis of six shipbuilding projects based on data from interviews, project documentation and clips from the media press. Findings – In ETO supply chains, the engineering and production activities involve mutual interdependences that need to be coordinated. The findings suggest that both the integration of engineering and production and the production capability are the most critical factors influencing coordination in an ETO supply chain. Research limitations/implications – The study was carried out within shipbuilding projects as a setting to represent the ETO domain. To extend the findings, further research can examine other types of projects, such as: oil and gas, construction, military and aerospace. Practical implications – In practice, there is no "one-fits-all" solution for coordination. Each project represents a unique context which has specific objectives, actors and constraints. From that perspective, this study provides a basis to comprehend coordination in a complex setting. Originality/value – This study builds knowledge upon coordination by generating a number of propositions regarding the effectiveness of coordination on avoiding delays in complex projects carried out in ETO supply chains. Focusing on the engineering and production activities, the authors extend the existing theory by demonstrating that coordination can vary according to the level of several moderating factors.